Analisis Penggunaan Majas Pada Anggota Stand Up Comedy di Youtube - Sahrina Sahrina; faridah faridah; Rina Devianty (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The research that has been carried out is entitled "Analysis of the Use of Figures of Speech among Stand Up Comedy Members" which aims to describe the style of language spoken by comics and explain the meaning of the language styles used, including comparative, affirmative, contradictory and satirical figures of speech. The theory in this research is a figure of speech. This type of research is qualitative, the source of the research data is the Youtube application, the research data is in the form of quotations of words that can be classified into a figure of speech based on the speech delivered by the comics.The research data collection technique is (1) Watching stand up comedy shows performed by comics on Youtube (2) Note down words that contain figures of speech and explain the meaning of figures of speech that have been conveyed by the comics (3) Collect secondary data by documenting things related to stand up comedy videos. The data analysis technique is carried out by (1) sorting the collected data, namely taking what is needed and what is not needed (2) marking the figures of speech used by comics when performing comedy with the aim of determining similar figures of speech (3) Drawing conclusions from the results of the analysis data obtained from start to finish. Based on data analysis and discussion, twenty five narrative research results were obtained